Central Bank Participation in Currency Options Markets - Breuer, Peter (IMF Working Papers; Working Paper, 1999)
This paper analyzes whether and how central banks can use currency options to lower exchange rate volatility and maintain (implicit) target zones in foreign exchange markets. It argues that selling rather than buying options will result in market makers dynamically hedging their long option exposure in a stabilizing manner, consistent with the first objective. Selling a 'strangle' allows a central bank to increase the credibility of its commitment to a target zone, and could have a lower expected cost than spot market interventions. However, this strategy also exposes the central bank to an unlimited loss potential.